Second Five Year Plan (1956-57 1960-61) Zalawad District Bombay State - Planning Commission (Planning Commission, 1956)
The district of Zalawad was constituted in the year 1948, consequent on the formation of the new State of Saurashtra. the district is composed of the territories of the former states of Dhrangadhra, Limbdi, Wadhwan Lakhtar, Muli, Sayla, Bajana, Patdi, Chuda, Vanod, Vithalgadh Anandpur, Rajpur and Jainabad, parts of Raisankali, Bhoika, Zinzuwada, Dasada, Chotila and part of Paliad Thana of Western India State’s Agency.
Bombay State